2022
DOI: 10.1787/2de3cd7d-en
|View full text |Cite
|
Sign up to set email alerts
|

Expanding access to finance to boost growth and reduce inequalities in Mexico

Abstract: Working Papers should not be reported as representing the official views of the OECD or of its member countries. The opinions expressed and arguments employed are those of the author(s).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…South Africa also endorsed DIF despite having a low "mobile money penetration rate" [21] relative to other developing countries because sub-Saharan Africa-based studies also showed consistent findings about DIF on the economy. In 2022, the author of OECD's report "Expanding access to finance to boost growth and reduce inequalities in Mexico" appealed to the problem of unequal access to financial services and underlined the resultant obstruction to SMEs and the wider economy [19] and called to "strengthening financial education and digital literacy" to boost its metamorphosis.…”
Section: Datamentioning
confidence: 99%
“…South Africa also endorsed DIF despite having a low "mobile money penetration rate" [21] relative to other developing countries because sub-Saharan Africa-based studies also showed consistent findings about DIF on the economy. In 2022, the author of OECD's report "Expanding access to finance to boost growth and reduce inequalities in Mexico" appealed to the problem of unequal access to financial services and underlined the resultant obstruction to SMEs and the wider economy [19] and called to "strengthening financial education and digital literacy" to boost its metamorphosis.…”
Section: Datamentioning
confidence: 99%